Analisis Green Marketing dan Brand Image Terhadap Keputusan Pembelian Produk Garnier di Surabaya - Anarta, Ahmad Dimar; Supriyono (Jurnal Economic Resource, 2025)
Environmental pollution due to plastic waste is a serious global problem because it accelerates ecosystem damage. Companies like Garnier play an important role in reducing these impacts using eco-friendly packaging and the application of sustainability principles in their production. This study aims to analyze the impact of green marketing and brand image on the decision to purchase Garnier products through TikTok in the city of Surabaya. The quantitative method was used in conjunction with the purposive sampling technique for 99 respondents. The analysis was carried out using PLS-SEM through SmartPLS software. The results show that green marketing and brand image have a significant positive influence on purchasing decisions.